Analisis Pengaruh Fasilitas Kerja Dan Disiplin Kerja Terhadap Komitmen Organisasi Pada Anggota Kepolisisan POLRES Tanah Bumbu - Heriyanto . Heriyanto; Siti Mardah; Netty Norhayati; Rahmi Widyanti (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2020)
Mastery of work materials that are always left behind by the development of science and technology and the weak level of discipline of employees have an effect on improving performance, so a study is needed to measure the effect of work facilities and work discipline on organizational commitment to members of the Tanah Bumbu Police.The aims of this study are: 1) work facilities partially affect the organizational commitment of police members at the POLRES Tanah Bumbu, 2) whether work discipline partially affects the organizational commitment of police members at the POLRES Tanah Bumbu and 3) whether work facilities and work discipline are simultaneously affect the Organizational Commitment of Police Members at the POLRESTanah Bumbu The method used in this study is quantitative with a sample of 50 respondents using multiple regression analysis.The results of this study are 1) The work facilities variable partially has no significant effect on Organizational Commitment of Police Members (0.201 > 0.05), 2) There is a significant partial effect of work discipline on Organizational Commitment of Police Members (0.001 < 0.05) and 3 ) There is a simultaneous (together) significant effect between work facilities and work discipline on Member Organizational Commitment (0.001 <0.05). The finding in this study is that complete work facilities if not accompanied by high discipline will have less effect on organizational commitment.